1998
DOI: 10.1159/000013316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramadan Fasting on Moslem Kidney Transplant Recipients

Abstract: This study was carried out to find out whether Ramadan fasting would affect the renal function in kidney transplant recipients with normal or impaired graft function. Twenty-three transplant recipients, 17 with a normal function and 6 with an impaired but stable function with plasma creatinine levels not exceeding 300 mmol/l, were included in this study. The mean posttransplant period was 2.0 (range 0.6–6.3) years. Urinary and serum biochemical parameters, ciclosporin A level, and hematocrit were checked weekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 4 publications
3
34
0
Order By: Relevance
“…The long-term dietary restrictions can lead to alteration in hematocrit and electrolyte imbalance. 1 Additionally increased incidence of central retinal vein occlusion during religious fasting has been reported. 2 To the best of our knowledge, there is only one study in the literature on fasting and IOP, which concluded that fasting in healthy adults did not alter the diurnal intraocular pressure in healthy adults.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term dietary restrictions can lead to alteration in hematocrit and electrolyte imbalance. 1 Additionally increased incidence of central retinal vein occlusion during religious fasting has been reported. 2 To the best of our knowledge, there is only one study in the literature on fasting and IOP, which concluded that fasting in healthy adults did not alter the diurnal intraocular pressure in healthy adults.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] We also noted no change in eGFR after fasting for 3 consecutive Ramadans, even after adjusting for age, presence of diabetes mellitus, baseline GFR, proteinuria, or time after transplant. There were no significant differences between fasters and nonfasters regarding changes in GFR, mean arterial pressure (MAP), and urinary protein excretion between baseline and the third Ramadan.…”
Section: Discussionmentioning
confidence: 88%
“…Many reports have focused on its effect on kidney graft recipients; however, all the previous reports have dealt with fasting during months other than August. [1][2][3][4][5][6][7][8][9] This study is different in that it was performed during Ramadan of 2011, which occurred during August in Riyadh, Saudi Arabia, which has one of the hottest climates in the world. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Muslims observing the fast must not only abstain from eating and drinking, but also from taking oral medications, smoking, as well as receiving intravenous fluids and nutrients. [1] The quantity of fluid and food intake also changes during Ramadan. Volume deficit and dehydration can occur, especially in the long summer days.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Accordingly, some publications reported that there are adverse affects of fasting during Ramadan on the electrolyte balance and hematocrit level. [1] In our study, we compared the metabolic state of known epilepsy patients who suffered a seizure during Ramadan or during a non-fasting period (the control group).…”
Section: Introductionmentioning
confidence: 99%